Rollout of quality assurance interventions in labor room in two districts of Bihar, India - Jyoti Sharma; Sutapa B Neogi; Preeti Negandhi; Monika Chauhan; Siddharth Reddy; Ghanshyam Sethy (Wolters Kluwer Medknow Publications, 2016)
Background: Quality of care at the facilities during childbirth remains a major concern. Improved quality could have the greatest dividend in saving maternal and newborn lives. Objective: The objective of this study was to implement quality assurance measures in the labor rooms of select public health facilities in two districts of Bihar. Methods: The labor room quality assurance intervention was implemented in two districts, Gaya and Purnea in Bihar. Health facilities having >200 deliveries/month were assessed using labor room quality assurance checklist developed by the Ministry of Health and Family Welfare. The critical gaps affecting service delivery were identified, and a list of priority actions for quality improvement was developed. An intervention model was rolled out in consultation with the district authorities focusing on the building blocks of the health system. The interventions were implemented from August 2014 to March 2016 in selected facilities after which an assessment was conducted. Results: Initial assessment of labor room was conducted in 24 facilities. After 2 years of intervention, there was a definite improvement in quality assurance scores in most facilities. The infection control scores increased by 20 points in Gaya (from 40 to 59.9) and 10 points in Purnea (from 57.6 to 67.1). The highest gain in scores was observed in quality management component in Gaya (from 6.2 to 58.2). The model attempted to incorporate all the elements of the health system to ensure scalability and sustainability. Conclusion: It is possible to have an implementable quality assurance mechanism within public health system with sustained efforts and commitment.